EFFECT OF TIDEGLUSIB WITH BONE GRAFTING ON NEW BONE FORMATION - Ufuk Taşdemir; Berrin İyilikci; Alper Kızıldağ; Özlem Özmen (Cumhuriyet University, 2021)
ABSTRACT Objectives: The goal of this study was to observe the regenerative potential of Tideglusib in combination with autogenous and xenograft mandibular defects in rats. Material Methods: Our study consists of five groups: one control and four experimental. In 40 Wistar albino rats, 5-mm-diameter critical bone defects were created at the angle of the mandible. In the control group, the defect was not filled. The defects were grafted only Xenograft in Group 1, with Xenograft and tideglusib in Group 2, and with only autogenous bone graft in Group3, and with autogenous bone graft mixed with tideglusib in Group 4. Results: Sterological analyses revealed that enhanced new bone formation in the Group 4 compare to Control and Group 1. Immunohistochemically marked expressions of BMP-2 and VEGF were observed in Group 4. Conclusions: Our results demonstrated that Tideglusib, in combination with bone grafting has an adjuvant effect on BMP-2 and VEGF-A expressions that may accelerate bone regeneration.